Formulation and In Vitro-In Vivo Correlation of Timolol Maleate Ocular Insert - Thakral, Sunil; Issarani, Roshan; Nagori, Badri P. (Indonesian Journal of Clinical Pharmacy, 2015)
The concept of in-vitro and in-vivo correlation studies was used in pharmaceutical research because a simple in-vitro release study on a drug product will be insufficient to predict its therapeutic efficiency. Therefore, correlation between in-vitro release behavior of a drug and its in-vivo absorption in rabbits must be demonstrated experimentally to reproduce therapeutic response. Aim of the study was to study the in vitro and in vivo evaluation and correlation of timolol maleate ocular insert. Timolol maleate ocular inserts were prepared by solvent casting method using guar gum in different proportions (0.25% w/v, 0.50% w/v, 0.75 % w/v, and 1.0% w/v). In vitro transcorneal permeation study was performed on goat cornea using modified Franz diffusion cell. The in vivo study was done using New Zeland albino rabbits and the in vitro invivo correlation (IVIVC) was determined by plotting a graph of in vivo drug release was plotted against in vitro release to determine the correlation. The cumulative % drug releases from the formulation ranged from 50.22±1.41 to 97.72±0.67over a period of 24 h. In vivo release of the timolol maleate from the optimized ocular inserts F2, through conjunctival cul-de-sac of rabbits was 76.03±1.43 at the end of 24 h. A high value of correlation coefficient (r2=0.9965) suggested good correlation between the in vitro-in vivo data of the timolol maleate ocular insert.Keywords: Guar gum, IVIVC, in vitro transcorneal permeation study, ocular insert, timolol maleate Formulasi dan Korelasi In vitro-In vivo pada Timolol Maleat dengan Penyisipan OkularKonsep studi korelasi in-vitro dan in-vivo telah digunakan dalam penelitian farmasi karena studi invitro yang sederhana pada produk obat tidak cukup untuk memprediksi efisiensi terapi. Oleh karena itu, korelasi antara pelepasan in vitro obat dan penyerapan secara in vivo pada kelinci harus dapat didemonstrasikan secara eksperimental untuk menghasilkan respons terapi. Tujuan penelitian ini adalah mengevaluasi formulasi dan korelasi in vitro dan invivo pada timolol maleat dengan penyisipan okular. Penyisipan okular timolol maleat disiapkan dengan metode pemilihan pelarut menggunakan guar gum pada proporsi berbeda (0,25% w/v, 0,50% w/v, 0,75 % w/v, dan 1,0% w/v). Permeasi transkorneal in vitro dilakukan pada kornea kambing menggunakan modifikasi difusi sel Franz. Studi in vivo dilakukan pada kelinci albino New Zeland dan korelasi invitro invivo (IVIVC) ditentukan dengan pelepasan in vivoobat yang diplot pada grafik yang dihubungkan dengan pelepasan in vitro untuk menentukan korelasi. Pelepasan kumulatif obat (%) dari formulasi memiliki rentang antara 50,22±1,41 sampai 97,72±0,67 pada lebih dari periode 24 jam. Pelepasan in vivo timolol maleat dari penyisipan okular teroptimasi F2, melalui konjungsi kul-de-sak pada kelinci yaitu 76,03±1,43 pada akhir periode 24 jam. Nilai yang tinggi dari koefisien korelasi (r2=0,9965) menunjukkan korelasi yang baik antara invitro dan invivo data penyisipan okular pada timolol maleat.Kata kunci: Guar gum, IVIVC, penyisipan okular, studi permeasi transkorneal in vitro, timolol maleat